External pressure-triggering of star formation in a disc galaxy: a template for positive feedback - Bieri, Rebekka; Dubois, Yohan; Silk, Joseph; Mamon, Gary Allan; Gaibler, Volker (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. Feedback from active galactic nuclei (AGN) has often been invoked both in simulations and in interpreting observations for regulating star formation
Published: 04 December 2015
Gesehen am 12.05.2020